Development and assessment of an intestinal tri-cellular model to investigate the pro/anti-inflammatory potential of digested foods - Ramal-Sanchez, Marina; Bravo-Trippetta, Chiara; D’Antonio, Veronica; Corvaglia, Elena; Kämpfer, Angela A. M.; Schins, Roel P. F.; Serafini, Mauro; Angelino, Donato (Frontiers in Immunology, 2025)
IntroductionImmunonutrition, defined as the potential of foods, nutrients and dietary patterns to modulate the immune system activity, has been proposed as a strategy to enhance the immune response in both metabolic and immune-mediated diseases. However, the anti-/pro-inflammatory role of foods and diets is far to be fully ascertained, and thus there is a continued needed for appropriate in vitro cell-culture models to investigate the role of foods in modulating cell-mediated inflammatory processes. This study aims to develop and test an in vitro tri-culture model, simulating the complexity of the intestinal tract and its multiple cell interactions.MethodsTo achieve this, the intestinal epithelial barrier was established by co-culturing human Caco-2 enterocyte-like and HT29-MTX-E12 mucus producing goblet-like colon cells, then adding human monocyte THP-1 cells to the basolateral compartment. The integrity and stability of the epithelial barrier were monitored and the inflammatory response of the model was assessed using various stressors at different concentrations, both individually and in combination (phorbol-12- myristate-13-acetate or PMA, and lipopolysaccharide or LPS), in terms of cytokines production. To test the model, different concentrations of in vitro digested broccoli (BD) were added to the apical section of the model.ResultsSupernatants from the basolateral compartment were collected and analyzed for cytokines production (IL-6, TNF-α, IL-12p70, IL-18 and IL-8) using automated ELISA (ELLA). Additionally, ZO-1 protein from the tight junctions of epithelial cells was analyzed by flow cytometry. The results indicated that 100 nM PMA added to the whole model for 20 h was the best stressor to simulate a mild-inflammatory status of the gut. Following treatment with BD, IL-6, TNF-α, IL-8 and IL-18 were significantly reduced compared to the control group, while ZO-1 expression increased at the lowest BD concentration.ConclusionsThese findings confirm the feasibility of the model for assessing the effects of food digesta on specific cytokines and permeability markers, representing a valuable strategy for investigating the role of foods in modulating the inflammatory response. The results obtained may support dietary strategies aimed at promoting wellbeing and preventing inflammatory-related metabolic diseases.